Hubungan Antara Efektivitas Pelaksanaan Otonomi Daerah Dengan Kewenangan Kepala Daerah - Dangeubun, Marvey Junus (Jurnal Sosial dan Teknologi Terapan AMATA, 2024)
This article aims to determine and explain the relationship between the effectiveness of the implementation of regional autonomy and the authority of regional heads as civil service development officials in the regions. Regulations in all Laws on Regional Government have placed the role of Regional Heads in a very strategic position considering that Regional Heads are an important component for the success of national development. because regional government is a subsystem of national or state government. The effectiveness of state government depends on the effectiveness of regional government administration. The success of regional leadership determines the success of national leadership. From an organizational and management perspective, the Regional Head is a figure or manager who determines the effectiveness of achieving regional government organizational goals